Optimization of Broadcast Time to Increase Instagram Create Case Study Lontara.App - Larasati Nurul Iman (Jurnal Syntax Admiration, 2023)
This study aims to determine the impact of using hashtags and optimizing broadcast time on the reach of Lontara.app Instagram. The type of data carried out in this study is quantitative data in the form of reach figures seen on Lontara.app Instagram insights. This research sees the difference between before-using broadcast time optimization and after-broadcast posts at the highest and second-highest time of followers in Lontara.App instagram account. From this research, there has been an increase in the reach of the Instagram Lontara.app by optimizing broadcast time with the aim that the content created can be seen by potential customers or consumers right when they are active. The results of this study indicate an 81.76% increase in Instagram Reach for the use optimization of broadcast time using the highest active time from Instagram Followers.